2013
DOI: 10.1104/pp.113.224287
|View full text |Cite
|
Sign up to set email alerts
|

The Gene sml0013 of Synechocystis Species Strain PCC 6803 Encodes for a Novel Subunit of the NAD(P)H Oxidoreductase or Complex I That Is Ubiquitously Distributed among Cyanobacteria  

Abstract: The NAD(P)H oxidoreductase or complex I (NDH1) complex participates in many processes such as respiration, cyclic electron flow, and inorganic carbon concentration in the cyanobacterial cell. Despite immense progress in our understanding of the structure-function relation of the cyanobacterial NDH1 complex, the subunits catalyzing NAD(P)H docking and oxidation are still missing. The gene sml0013 of Synechocystis 6803 encodes for a small protein of unknown function for which homologs exist in all completely kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 44 publications
(66 reference statements)
3
29
0
Order By: Relevance
“…The transposon insertion occurred at position 3188117 of the Synechocystis 6803 genome (49). This implies that inactivation of ndhP impairs NDH-CET activity, as suggested recently by Schwarz et al (24).…”
Section: Isolation Of Ndh-cet-defective Mutants-supporting
confidence: 55%
See 3 more Smart Citations
“…The transposon insertion occurred at position 3188117 of the Synechocystis 6803 genome (49). This implies that inactivation of ndhP impairs NDH-CET activity, as suggested recently by Schwarz et al (24).…”
Section: Isolation Of Ndh-cet-defective Mutants-supporting
confidence: 55%
“…The NDH-1L complex is involved in respiration and NDH-CET (3), which explains the impairment of these activities in the ⌬ndhP mutant of Synechocystis 6803 (Figs. 1B and 2, D-F) (24).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Nowaczyk et al (2011) reported two novel small subunits, NdhP and NdhQ, which were included in the purified NDH-1L complex by Ni 2+ affinity chromatography and sizeexclusion chromatography from T. elongatus. Recently, it has been demonstrated that NdhP and NdhQ are involved in respiration and CET and are required to stabilize the NDH-1L complex (Schwarz et al, 2013;Wulfhorst et al, 2014;Zhang et al, 2014;Zhao et al, 2015). In recent years, it has been reported that the newly identified OPS subunit, NdhS from Arabidopsis (also known as CRR31) or from Synechocystis 6803 contains Src homology 3 domain-like fold, which serves as the ferredoxin (Fd) docking site domain (Yamamoto et al, 2011;Battchikova et al, 2011b;Yamamoto and Shikanai, 2013), and the authors suggested that the chloroplast NDH complex could accept electrons from Fd rather than NAD(P)H. By studying the purified NDH-1L complex from the thermophilic cyanobacterium T. elongatus, we demonstrated that NDH-1L Figure 1.…”
mentioning
confidence: 99%